5-Na/ZnO doped mesoporous silica as reusable solid catalyst for biodiesel production via transesterification of virgin cottonseed oil. (April 2019) - Malhotra, Rashi; Ali, Amjad
Abstract: 5-Na/ZnO loaded SBA-15 has been prepared by one-pot method in atmospheric conditions (without employing hydrothermal treatment) and following wet impregnation method. The prepared catalyst was characterised by using several techniques viz., BET method for determination of surface area, FE-SEM for morphology of catalyst, XPS study to determine the oxidation state of constituent elements. The catalyst was utilised for transesterification from virgin cotton seed oil and the catalyst activity was dependant on its basic strength. Under optimal reaction conditions of catalyst amount 12 wt%, methanol to oil molar ratio of 24:1 at reaction temperature of 65 °C, the prepared catalyst yielded > 98% fatty acid methyl ester in 4 h of reaction duration. The catalyst was able to yield conversion level as good as ∼74% even in 5 th cycle after regeneration. Leaching of < 5 ppm metal content was observed, in 4 th and 5 th cycle, which was within the ASTM specified limitations. The thermodynamic parameters for the reaction, viz., activation energy Ea, ΔH ‡, ΔS ‡, ΔG ‡ were calculated as 77.3 kJ mol −1, 74.2 kJ mol −1, -0.064 kJ mol −1 and,  + 93.2 kJ mol −1 respectively. Graphical abstract: Image 1 Highlights: Synthesis of SBA-15 and impregnation of 5-Na/ZnO was performed in single step. In situ method of synthesis saved lot of time and energy consumption compared to 2-step synthesis. Prepared catalyst was employed for biodiesel production and reused for 5 consecutive runs. The catalyst activity was found to be a function of its basic strength.